Uncovering Subclinical Cardiac Involvement in VEDOSS: An Echocardiographic Driven Study - Eugenio Capparelli; Eleonora Zaccara; Ilaria Suardi; Antonella Laria; Laura Castelnovo; Eleonora Mauric; Daniela Bompane; Antonio Tamburello; Maria Iacovantuono; Maria Sole Chimenti; Antonino Mazzone; Paola Faggioli (Sclerosis)
Background: The 2011 Very Early Diagnosis of Systemic Sclerosis (VEDOSS) criteria include both patients at risk of progression and those with mild non-progressive forms of SSc. Early diastolic and systolic dysfunction can indicate myocardial fibrosis in SSc patients, yet data on myocardial impairment in the VEDOSS population are limited. Objectives: This study aimed to identify subclinical echocardiographic changes and predictive markers of cardiac dysfunction in both very early and mild-longstanding forms of VEDOSS. Methods: We conducted a cross-sectional observational study involving 61 patients meeting VEDOSS criteria followed up regularly within our Scleroderma referral center. Patients were categorized as early VEDOSS (e-VEDOSS) or mild-longstanding VEDOSS (ml-VEDOSS) based on disease duration (≥10 years). We analyzed clinical and demographic data, focusing on echocardiographic parameters such as the E/A ratio and left ventricular (LV) thickness. Statistical analyses included chi-square, Fischer exact, and student’s t tests, with a significance threshold of p < 0.05. Results: ml-VEDOSS patients were older and reported a higher burden of comorbidities. Autoantibody-positive patients exhibited lower E/A ratios and increased left atrial size. Late nailfold videocapillaroscopic pattern patients exhibited increased PWED thickening and aortic valve insufficiency. Notably, patients undergoing vasodilators experienced larger right atrial volume, while patients receiving Renin-Angiotensin-Aldosterone System (RAAS) inhibitors reported reduced E/A ratio. Multivariable analysis confirmed DLCO% as the sole predictor of both diastolic and systolic impairment in VEDOSS population. Conclusions: Careful monitoring of cardiac function in VEDOSS patients is crucial as subclinical alterations may occur even in the absence of symptoms. DLCO% emerged as an important predictor of LV diastolic dysfunction.